The Role of Mass Media in Extreme Situations - Tergembaeva К.И. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
With independence, Kazakhstan needed to restore all key areas of public relations, especially it was necessary to review and create a civil defense system in the country and protect the population and territory from natural and man-made emergencies. The Committee for Emergency Situations, the Ministry of Internal Affairs of the Republic of Kazakhstan, with its territorial divisions and subordinate organizations, forces and means, is an operational service for responding to emergency situations of a natural and man-made nature. This scientific article discusses how the media in extreme situations work with operational services and provide the audience with the necessary information. The author gives examples of the work of journalists in emergency situations, analyzes them, comes to certain conclusions and gives his recommendations.